Centration assessment of an extended depth of focus contact lens for myopic progression control. Issue 1 (February 2023) - Rizzo, Giulia Carlotta; Di Vizio, Assunta; Versaci, Francesco; Przekoracka, Katarzyna; Tavazzi, Silvia; Zeri, Fabrizio
Abstract: Purpose: To evaluate the accuracy and the inter and intra-observer reliability of the centration assessment of extended depth of focus (EDOF) contact lenses (CL) using corneal topography. Method: EDOF soft CLs (Mylo, Mark'Ennovy) were fitted on thirty-three myopic students (25 females), aged 19–28 years (22.7 ± 2.0 years). For any EDOF CL, a topography over the CL and a slit lamp (SL) digital picture were taken in random order. For the topographic images, the position of the EDOF CL centre, with respect to the pupil centre, was detected by two different practitioners (one newly graduated and one with more than 20 years of clinical experience respectively) and repeated after 15 days. This measurement was compared to the one taken through the SL, considered as the gold standard, and assessed using the instrument software. Results: EDOF CLs resulted decentred inferiorly and temporally ranging, in the case of slit lamp assessment, between −0.27 ± 0.19 and 0.22 ± 0.23 mm horizontally and between −0.12 ± 0.31 and −0.17 ± 0.34 mm vertically, for the right and left eye respectively. The accuracy of the topographic assessment in determining EDOF CL centration was found to be very good compared to the SL assessment. No differences were found for the left eye, whereas in the right eye, a less temporally decentred position of the CL was detected by the topographical method (p < 0.05). However, this difference appeared clinically negligible (0.14 ± 0.22 mm). Inter-observer reliability (the differences between the two practitioners in assessing the EDOF centre) resulted significant only for the vertical coordinates of the centre position (p < 0.05). Concerning intra-observer reliability, better coefficient of precision and reliability between measurements within the same session were achieved by the more experienced practitioner, as well as a better level of the intraclass correlation coefficient in test–retest. Conclusion: The centration of the EDOF CL investigated in this study can be accurately detected by a corneal topography performed over CLs. Inter-observer reliability resulted good whereas the intra-observer reliability resulted partially affected by the level of clinical experience of the practitioner.